2008
DOI: 10.4143/crt.2008.40.3.127
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Morphogenesis Protein-2 (BMP-2) is Associated with Progression to Metastatic Disease in Gastric Cancer

Abstract: Purpose: Bone Morphogenetic Proteins (BMPs) are members of the TGF-β superfamily and it has been demonstrated that BMPs enhance migration, invasion and metastasis. The purpose of this study was to identify the association between the serum BMP-2 level and the progression status of gastric cancer.Materials and Methods: Fifty-five patients with metastatic gastric cancer (metastatic disease group), six patients with early gastric cancer without lymph node metastasis (the EGC group), and ten healthy control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The prognostic impact of BMP-2 levels in cancer patients has been evaluated in some studies (Park et al, 2008;Ma et al, 2010). Using immunohistochemical analysis, Ma et al evaluated the influence of intratumoral BMP-2 on five-year survival in 100 patients with epithelial ovarian cancer, showing that the median five-year survival was significantly longer in the groups with a low intratumoral BMP-2 staining intensity (40.32%) than that in the group with tumors expressing high levels of BMP-2 (18.42%, P=0.023) .…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of BMP-2 levels in cancer patients has been evaluated in some studies (Park et al, 2008;Ma et al, 2010). Using immunohistochemical analysis, Ma et al evaluated the influence of intratumoral BMP-2 on five-year survival in 100 patients with epithelial ovarian cancer, showing that the median five-year survival was significantly longer in the groups with a low intratumoral BMP-2 staining intensity (40.32%) than that in the group with tumors expressing high levels of BMP-2 (18.42%, P=0.023) .…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10] It is furthermore known that BMPs not only have an important role in the iron sensing pathway but are also involved in the development and progression of different kinds of cancer. [11][12][13] We recently demonstrated that BMP4 promotes the progression of hepatocellular carcinoma (HCC).14 Noteworthy, up to now the impact of enhanced BMP expression on (changes in) iron metabolism in HCC, one of the most common cancers worldwide, 15 has not been addressed. Thus, one may hypothesize that patients with enhanced BMP expression levels develop anemia through increased levels of hepcidin, which is responsible for internalization and degradation of ferroportin to limit intestinal iron uptake.…”
mentioning
confidence: 99%
“…6,[8][9][10] It is furthermore known that BMPs not only have an important role in the iron sensing pathway but are also involved in the development and progression of different kinds of cancer. [11][12][13] We recently demonstrated that BMP4 promotes the progression of hepatocellular carcinoma (HCC).…”
mentioning
confidence: 99%
“…clinically, Bmp2 has been used for various therapeutic interventions, such as bone defects, non-union fracture, spinal fusion, osteoporosis and root canal surgery (3). apart from bone disease, Bmp2 has been shown to be associated with invasion and metastasis of several tumor cell lines (15,19,20) and is used as a prognostic marker for specific tumors (21). Moreover, it is involved in vascular physiology as a proatherogenic mediator in the arterial wall (4).…”
Section: Discussionmentioning
confidence: 99%